1996
DOI: 10.1111/j.1600-0447.1996.tb09860.x
|View full text |Cite
|
Sign up to set email alerts
|

Dementia of depression or depression of dementia in stroke?

Abstract: This study describes the correlation between changes in mood symptoms assessed by the Hamilton Depression Rating Scale (HDRS) and intellectual impairment assessed by the Brief Cognitive Rating Scale (BCRS) and Mattis Dementia Rating Scale (MDRS) in 166 unselected 1-year survivors after stroke, in whom post-stroke depression (PSD) has previously been described and validated. The course of intellectual impairment associated with PSD was compared with the course of intellectual impairment in non-PSD patients. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
22
0
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 23 publications
4
22
0
4
Order By: Relevance
“…In addition, for patients with left hemisphere lesions, there was a significant correlation between severity of cognitive impairment and Beck Depression Inventory score, whereas the correlation was nonsignificant in the right hemisphere. 7 Similar findings have also been reported by Morris et al 8 and Andersen et al 9 In spite of this general concurrence of findings, all prior double-blind treatment trials have failed to show an improvement in cognitive function among patients with poststroke depression who were given active antidepressant therapy. 9 -11 This finding led Andersen et al 9 to suggest that the cognitive impairment may be the cause of depression.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…In addition, for patients with left hemisphere lesions, there was a significant correlation between severity of cognitive impairment and Beck Depression Inventory score, whereas the correlation was nonsignificant in the right hemisphere. 7 Similar findings have also been reported by Morris et al 8 and Andersen et al 9 In spite of this general concurrence of findings, all prior double-blind treatment trials have failed to show an improvement in cognitive function among patients with poststroke depression who were given active antidepressant therapy. 9 -11 This finding led Andersen et al 9 to suggest that the cognitive impairment may be the cause of depression.…”
supporting
confidence: 69%
“…7 Similar findings have also been reported by Morris et al 8 and Andersen et al 9 In spite of this general concurrence of findings, all prior double-blind treatment trials have failed to show an improvement in cognitive function among patients with poststroke depression who were given active antidepressant therapy. 9 -11 This finding led Andersen et al 9 to suggest that the cognitive impairment may be the cause of depression. We subsequently refuted this hypothesis by demonstrating that among patients not treated for depression, there was a correspondence between depression and cognitive function.…”
supporting
confidence: 69%
“…40 Further analysis shows that the risk is striking for subjects reporting a previous stroke (ORϭ10.77; CI 2.23 to 80.60). Depression may be a premonitory syndrome for VaD in stroke patients 41 or a marker of the importance of cerebral damage.…”
Section: Discussionmentioning
confidence: 99%
“…Post-stroke cognitive impairment is also very common, where its cause is probably multi-factorial 5 . The role of mood changes in the genesis of post-stroke cognitive impairment remains controversial 6,7 , and there is also controversy regarding the outcome of cognitive impairment following mood impro v e m e n t 6 , 8 . A recent systematic review of p h a rmacological therapies of depression after stro k e concluded that there is no evidence of benefit of ant i d e p ressants in improving cognitive function 3 .…”
mentioning
confidence: 99%
“…A recent systematic review of p h a rmacological therapies of depression after stro k e concluded that there is no evidence of benefit of ant i d e p ressants in improving cognitive function 3 . Most of the studies have analyzed the effects of the tre a tment for depression based on the general intellectual function only, without focusing on specific cognitive domains [6][7][8][9] .…”
mentioning
confidence: 99%